Development of a Fourfold Multiplexed Opsonophagocytosis Assay for Pneumococcal Antibodies against Additional Serotypes and Discovery of Serological Subtypes in Streptococcus pneumoniae Serotype 20 - Burton, Robert L. (American Society for Microbiology, 2012)
Opsonophagocytic killing assays (OPAs) are important in vitro surrogate markers of protection in vaccine studies of Streptococcus pneumoniae. We have previously reported the development of a 4-fold multiplexed OPA (MOPA) for the 13 serotypes in Prevnar 13. Because new conjugate vaccines with increased valence are being developed, we developed 4-fold MOPAs for an additional 13 serotypes: serotypes 6C and 6D, plus the 11 serotypes contained in Pneumovax but not in Prevnar 13. A high level of nonspecific killing (NSK) was observed for three serotypes (10A, 15B, and 33F) in multiple batches of baby rabbit complement. The NSK could be reduced by preadsorbing the complement with encapsulated, as well as unencapsulated, pneumococcal strains. The MOPA results compared well with the results of single-serotype OPA for all serotypes except for serotype 3. For serotype 3, the results obtained from the MOPA format were ∼40% higher than those of the single-serotype format. Interassay precision of MOPA was determined with 5 serum samples, and the coefficient of variation was generally <30% for all serotypes. MOPA was also specific for all serotypes except for serotype 20; i.e., free homologous polysaccharide (PS), but not unrelated PS, could completely and efficiently inhibit opsonization. However, serotype 20 PS from ATCC could efficiently inhibit opsonization of one serotype 20 target strain but not three other type 20 target strains even at a high (>80 mg/liter) PS concentration. This suggests the presence of serologic heterogeneity among serotype 20 strains.